Evaluation of Radioactivity in Dusty Storm - A. S. Mohammed; N. A. Majeed; M. H. Nasaer; H. Hoshi; M. Abood (Journal of Madenat Alelem University College, 2013)
sample had been collected from the powder of the dusty storms which had been moved over Baghdad for a different months of a year 2011 by using metal containers that had manufactured locally and had been mounted over the roof of houses in particular regions of Baghdad (Kerkh and Risafa).The radioactive concentration of dust samples had been measured and analyzed by using the Gamma Spectroscopy analyzing System which consist of high purity Germanium detector of efficiency of 40 %, resolution 2keV at 1.332 MeV (Co-60) , DSA 2000 system which protective barrier made in Canberra Company , the developed Genie 2000Program and using personal computer. The measurement system for energy calibration and efficiency had been calibrated by using a standard point sources and standard source of a multi energy made by the American Canberra company. The Marnelli geometrical shape had been used to measure the activity of the samples. Results indicated the existence of the natural radioactive isotopes such as K-40, Be-7 which has been composed of as a result of the nuclear reaction between the Cosmic ray and some other elements of the atmosphere like Oxygen and Nitrogen besides the existence of radioactive isotopes which belongs to the natural Uranium series and the natural Thorium series. Highest measurements indicated the existence of industrial radioactive isotope Cs-137.The highest value of concentration for Be-7 was (381.5 Bq/kg) at Al-Shaab region, and the highest value of concentration for K-40 was (467.7 Bq/kg) and some other radioactive isotopes which belong to the series of U-238 as follows:- Bi -214 (32.6 Bq/kg), Pb-214 (33.6 Bq/kg), and radioactive isotopes which belong to the series Th-232 as follows:- Bi-212(18.6Bq/kg), Pb-212 (18.8Bq/kg),Ac-228 (30.3 Bq/kg),the highest value of concentration for the industrial Cs-137 was (26,8 Bq/kg) it was at Al-shaab region ,and this concentration is relatively high in comparison to the levels of normal concentration which exist in Iraqi soil. This concentration of radioactivity may be effect on human health due to internal and external exposures.